Improving engineering and thermal insulation properties of plastering mortar with natural rubber - Poonsawat, W.; Seesook, R., Horpibulsuk, S. and Suddeepong, A. (Proceedings of the IRRDB International Rubber Conference 2023, 20-21 February 2023, IRRDB, Kuala Lumpur, Malaysia, pp. 100-105.)
The prospects of pre-vulcanised natural rubber latex in improving engineering properties and thermal conductivity resistance of plastering mortar were investigated. The effect of influence factors including dry rubber content to cement (r/c) ratio and water to cement (w/c) ratio on the basic engineering properties (flow, water retention and setting time) and coefficient of thermal conductivity were studied. The cement to fine-aggregate (c/f) ratio herein was imposed at 1:2.5 by the total volume of mortar. The r/c ratios of 0%, 2%, 3%, 4%, 5%, 6% and 7% by total weight of plastering mortar and w/c ratios of 0.65, 0.70 and 0.75 by total weight of mortar were tested. The engineering properties were evaluated for a curing period of 28-days for all samples. Using pre-vulcanised latex, the basic engineering properties of plastering mortar that met the specification requirement of Thailand Industrial Standard (TIS 1776-2542) were r/c = 3%, and 4% at w/c = 0.7, while r/c = 5%, 6% and 7% at w/c = 0.75. The compressive, flexural, and tensile strengths of plastering mortar with pre-vulcanised latex (PML) increased with an increase in r/c ratio up to the highest value at the optimum r/c ratio for all w/c ratios. Beyond the optimum r/c ratios, the strength decreased with further increases in in the r/c ratio. On the other hand, adhesion strength of PML improved up to the highest value at the optimum r/c ratio, which is r/c = 2%. As with the mechanical strength, the adhesion strength of PML decreased with an increasing r/c beyond the optimum ratio. The coefficient of thermal conductivity (k) of PML using pre-vulcanised latex decreased with increasing r/c ratio and has the lowest value at the optimum r/c ratio (r/c = 3%), thereafter increasing with an increase in the r/c beyond the optimum ratio, hence improving engineering properties and thermal conductivity resistance.
Keywords: Pre-vulcanised latex; Engineering properties of mortar; Coefficient thermal conductivity